2014
DOI: 10.7314/apjcp.2014.15.8.3715
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Efficacy of Tai Chi in Improving Quality of Life in Breast Cancer Survivors: a Systematic Review and Meta-analysis

Abstract: Background: It is controversial whether Tai Chi (TC) benefits breast cancer survivors (BCS) on quality of life (QoL). We therefore undertook a meta-analysis to assess this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…QOL, a common gauge of cancer treatment effect, is widely used to measure the health of breast cancer patients (70) QOL is a multidimensional assessment with physical (including function/disability and symptoms/complications concepts), mental (including emotional distress, psychological well-being, perceived cognitive functioning, and spiritual/existential concerns concepts) and social (including socioeconomic challenges, role/relationship changes, perceived support/satisfaction, and social participation concepts) domains (70). Yan's and Tao's systematic reviews found TCC failed to improve QOL in breast cancer survivors (71,72), but this study showed 12 weeks TCC had a positive influence on QOL. Three studies in Yan's systematic review were not included in this review because the intervention therapy of two studies (73,74) was Tai Chi combining aerobics, and another study (75) was a prospective longitudinal study from a larger randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…QOL, a common gauge of cancer treatment effect, is widely used to measure the health of breast cancer patients (70) QOL is a multidimensional assessment with physical (including function/disability and symptoms/complications concepts), mental (including emotional distress, psychological well-being, perceived cognitive functioning, and spiritual/existential concerns concepts) and social (including socioeconomic challenges, role/relationship changes, perceived support/satisfaction, and social participation concepts) domains (70). Yan's and Tao's systematic reviews found TCC failed to improve QOL in breast cancer survivors (71,72), but this study showed 12 weeks TCC had a positive influence on QOL. Three studies in Yan's systematic review were not included in this review because the intervention therapy of two studies (73,74) was Tai Chi combining aerobics, and another study (75) was a prospective longitudinal study from a larger randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…This raises an issue as cancer patients are in a vulnerable state of mind after diagnoses and the ethics of selling health supplements to patients are questionable especially when the efficacy of CAM use among breast cancer has been investigated and found to have varying results (Hajime et al, 2013;Yan et al, 2014). Although the results of multivariate analyses did not support this information source (other medical staff) as an independent factor influencing CAM use, this may be due to lack of power of the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to yoga, tai chi and qigong have been less frequently studied in cancer but have increasingly received attention after a landmark study published in the New England Journal of Medicine suggested therapeutic benefits in patients with fibromyalgia with a single-blinded RCT design [71]. Yet, findings in the cancer literature are believed to be mixed at this stage as two recent meta-analyses (one involving 5 RCT’s of 407 women with breast cancer [72] and one including 13 RCT’s with 592 patients with mixed cancer types [63]) suggested. Both independent reviews concluded that, although treatment gains are evident, caution is warranted due to methodological constraints and the small sample of included trials.…”
Section: Mind-body Practicesmentioning
confidence: 99%